Dampak Pengalaman, Skeptisisme Profesional, dan Kompetensi pada Kemampuan Auditor dalam Mendeteksi Kecurangan - Natalia, Ni Kadek Lia; Yenni Latrini, Made (E-Jurnal Akuntansi, 2021)
The auditor's ability to detect fraud is the auditor's ability to determine illegal acts that result in material misstatement in the financial statements which were done intentionally. In order for the auditor's ability to perform detection to increase, an experienced auditor, professional skepticism and competence is needed. The purpose of this study is to empirically prove the effect of experience, professional skepticism, and competence on the ability of auditors to detect fraud. This research was conducted at a Public Accountant Firm in Bali Province with a purposive sampling method of determining the sample. The number of samples analyzed in this study were 61 auditors. Data collection was carried out through interviews and questionnaires. The analysis technique used is multiple linear regression. Based on the analysis, it was found that experience, professional skepticism, and competence have a positive effect on the ability of auditors to detect fraud. Keywords: Experience; Professional Skepticism; Competence; Fraud Detection.